Exploring the factors that motivated University graduates from Vhembe District in Limpopo to complete their undergraduate degrees in set time - Makamu, Nkhensani Portia (My University, 2016)
Post 1994 has been characterised by an increase in access to higher education for different racial groups in South Africa. However, the increase in access seem not to correspond with the success rate of some students in higher education, as a significant number of black students fail to complete their degrees in set time. Anecdotal evidence indicates that some of the reasons highlighted for this failure include, the notion that students enter higher education “underprepared” for the transition, leading to some students failing to complete their studies within the set time, and some dropping out and / or getting academically excluded. Therefore, the aim of the study was to explore the factors that motivated university graduates from Vhembe District in Limpopo to complete their university degrees in set time. The study employed an exploratory-descriptive design located within a qualitative research paradigm. A snowball sampling technique was used to select ten university graduates to participate in the study. A semi-structured interview schedule was employed as a research instrument, with in-depth, individual, face-to-face interviews used as a method of data collection. Qualitative data were analysed using thematic content analyses. The main findings of the study indicate that the factors that motivated university graduates from Vhembe District to complete their studies in set time included the following: being goal oriented, the desire to effectively compete in the job market, the need for independence, the desire to improve dire family circumstances, being bound by contract expectations attached to financial assistance and to defy the odd of associating poverty with no success. The conclusion drawn is that low socio-economic backgrounds of black students cannot be used as a predictive factor for their success and lack of, in higher education, as students were able to succeed against all odds and completed their degrees in set time. Recommendations are made in relation to future research. Key words: access to higher education, degree completion motivating factors, set time, black university graduates, Vhembe district – Limpopo, South Africa
In partial fulfilment of the requirements for the degree Bachelor of Social Work